2019
DOI: 10.1021/acs.chemmater.9b01435
|View full text |Cite
|
Sign up to set email alerts
|

Fast Rotational Dynamics in Argyrodite-Type Li6PS5X (X: Cl, Br, I) as Seen by 31P Nuclear Magnetic Relaxation—On Cation–Anion Coupled Transport in Thiophosphates

Abstract: Electrolytes with excellent ionic conductivity are needed for the development of safe and long-lasting all-solid-state batteries. Perfect candidates are Argyrodites, like Li 6 PS 5 X (X: Cl, Br, I), that show an ionic conductivity in the mS/cm range. Translational Li + diffusion in ceramic electrolytes is influenced by many factors such as crystal structure and defect chemistry. Considering thiophosphates, only little information is, however, available about the effects of rotational anion dynamics on Li + jum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
169
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 116 publications
(184 citation statements)
references
References 38 publications
10
169
2
Order By: Relevance
“…Owing to their high Li + ion conductivity at room temperature, sulfide-based materials are more promising electrolytes than oxide-based ones [ 159 , 160 , 161 , 162 , 163 , 164 , 165 , 166 , 167 , 168 , 169 , 170 , 171 , 172 , 173 , 174 , 175 , 176 , 177 , 178 , 179 , 180 , 181 , 182 , 183 , 184 , 185 , 186 , 187 , 188 , 189 , 190 , 191 , 192 , 193 , 194 , 195 , 196 , 197 , 198 , 199 , 200 , 201 , 202 , 203 , 204 , 205 , 206 , 207 , 208 ,…”
Section: Sulfide Solid Electrolytesmentioning
confidence: 99%
“…Owing to their high Li + ion conductivity at room temperature, sulfide-based materials are more promising electrolytes than oxide-based ones [ 159 , 160 , 161 , 162 , 163 , 164 , 165 , 166 , 167 , 168 , 169 , 170 , 171 , 172 , 173 , 174 , 175 , 176 , 177 , 178 , 179 , 180 , 181 , 182 , 183 , 184 , 185 , 186 , 187 , 188 , 189 , 190 , 191 , 192 , 193 , 194 , 195 , 196 , 197 , 198 , 199 , 200 , 201 , 202 , 203 , 204 , 205 , 206 , 207 , 208 ,…”
Section: Sulfide Solid Electrolytesmentioning
confidence: 99%
“…The role of rotation or vibration of polyhedra in ionic transport was discussed for several ionic conductors (e.g., hydride complex system [ 116 ] and argyrodite [ 117 ] ). The interaction of PS 4 tetrahedra with mobile lithium in LGPS was also discussed both experimentally and theoretically.…”
Section: Ionic Transportationmentioning
confidence: 99%
“…38,[49][50][51] Further, it was recently shown that additional polyhedral anion dynamics exist that are coupled to the Li + translation. 55 However, in the Li6PS5I series reported here, the Li + ion jumps and rotational dynamics are independent of each other, which beneficially prevents further complication of the analysis. In this work, the resulting lattice dynamics are assessed using the optical and acoustic modes of the dispersion relation.…”
Section: Results and Discusssionmentioning
confidence: 92%